Implementation of Integrated Science Course Program based on SAINS-Edu: Strengths and Weaknesses - Kadek Dwi Hendratma Gunawan (International Journal of Instructions and Language Studies, 2023)
This research described the Integrated Science course program based on SAINS-Edu to improve students' conceptual mastery. The program utilized pedagogical scaffolding and an artificial intelligence-based recommendation system in SAINS-Edu. The research design employed was an experimental study using a one-group pretest-posttest approach. Data were statistically analyzed to test mean differences using the t-test and to measure the impact using effect size. The data were also descriptively analyzed to highlight its strengths and weaknesses. The t-test results indicated a significant difference with value of 29,881. The effect size showed a high category with value of 4,775, signifying the effectiveness of this program in enhancing students' conceptual mastery. The program combines personalization and integration aspects that allow students to design integrated science learning in line with their interests and needs. The program's strengths encompass the inclusion of scaffolding, enhanced conceptual mastery, and higher-order thinking skills, along with student collaboration. Challenges include the time and resources required for software design, curriculum changes, and technological dependence. The study's findings provide a foundation for the development of similar course programs and the potential to enhance students' conceptual mastery in various learning contexts.